Impact of Lean System on Merchandizing Performance Excellence - Pathirathna, L.S.B.H.; Herath, H.M.R.P. (Faculty of Commerce and Management Studies, University of Kelaniya, 2015)
The study sets to achieve two objectives namely, identify the extent to which Lean system performance impact on Merchandizing Performance and bring recommends to horizontally replicate the research findings for similar organizations. The source of data for this study were both primary and secondary, and also the company data sources were assisted to fulfill this task. Since the company management encouraged for an effective outcome, the performance information was linked and opened throughout the research and the entire team involved taken for this program was consisted 160 merchandisers, where the total directly responding population was represented. The questionnaire was filled with main three categories, namely General Information, Lean System Performance, and Merchandising Performance and Lean System Performance was split into three sub areas, namely Safety and Ergonomics, Quality Management and Continuous Improvement. The data was analyzed through the SPSS software, and according to the findings, the Pearson’s correlation analysis justifies the positive correlations between safety and ergonomics, total quality management and continuous improvement with the Lean System Performance. The (R2) was 11.0%, which is the extent positively influenced to the Merchandizing Performance by the existing Lean System in the organization. The study also found out that the organization believes Lean System practices improve the long term business performance and this study establishes safety and ergonomics, quality management system and continuous improvement activity performance emanating from the implementation of lean system practices, and it impacts to the merchandizing performance as a front-end customer interface function of the organization.
Keywords: Lean Systems; Performance; Performance Excellence